Assessment of Knowledge and Associated Risk Factors Regarding Zoonotic Disease among Community Members of Siddharthanagar Municipality, Bhairahawa, Rupandehi (Global Journal of Medical Research, 2019)
Zoonoses are the common cause of disease occurrence in animals and humans in Bhairahawa. Many zoonotic disease such as Tuberculosis, Rabies, Heartworm, Brucella, Leptospira has been encountered in Veterinary Teaching Hospital, Institute of Agriculture and Animal Science (IAAS), Tribhuvan University from Bhairahawa periphery. We conducted a cross-sectional purposive random survey of total 303 villagers of Siddharthanagar Municipality, Bhairahawa, Rupandehi to study awareness status about zoonosis. Out of total individuals interviewed, 176 (58%) heard about the zoonotic disease and radio/television (37.5%) were the source of information. 66.7% female and 56.9% male knew about zoonosis. 72.9% of youths (30-50 years), 36.6% farmers, 33.33% Dalit and 40.2% Madheshi, 58.6% Hindu, 66.7% Buddhist, 66.7% of Christian knew about zoonosis. 86% of aware people knew about direct transmission rout of zoonotic disease, and 100%, 77.84%, 100%, 100% and 47.72% respondents knew about the contaminated food, milk, meat, bite, and secretion transmission route respectively.
Keywords: survey; zoonoses; siddharthanagar; veterinary teaching hospital; bhairahawa